Pengembangan Komik Strip Berdasarkan Urutan Kronologis Peristiwa Sebagai Media Pembelajaran Sejarah Di SMA - Nursepti Rani; Hera Hastuti (Jurnal Kronologi, 2021)
This study aims to develop a comic strip based on the chronological sequence of events as a valid medium for history learning in high school. The results showed that much of teachers surveyed considered comics to help motivate students to read and study, while they said comics could increase individual participation. This research is a research and development (R&D) using the ADDIE development model. The ADDIE development model is carried out at the Analyze, Design, and Development stages. Data were collected using product validity instruments which included content, language, and graphic validity. The data were analyzed using qualitative analysis and quantitative analysis. Based on the research that has been carried out, a comic strip has been produced with the following stages: (1) analysis, (2) design, (3) development. The analysis phase can be said to be an analysis of problems relevant to the problem consisting of needs analysis, material analysis and environmental analysis. The design stage is the stage carried out to compile a comic strip design including making a story summary design, story line design, initial comic design and editing using the Photoshop application. The development stage is the stage carried out to test the validity of the comic strip. Based on the product validity test, it is known that the comic strips produced are very valid from the material aspect and the media aspect. Thus, the resulting comic strip is feasible to be applied as a learning medium